Morphological and molecular study of the torrent catfishes (Sisoridae: Glyptosterninae) of Bhutan including the description of five new species - Thoni, Ryan J.; Gurung, Dhan B. (Zootaxa, 2018)
Torrent catfishes of the subfamily Glyptosterninae from Bhutan are examined based on morphological and molecular data. Five new species are described: Creteuchiloglanis bumdelingensis sp. nov., Exostoma mangdechhuensis sp. nov., Parachiloglanis benjii sp. nov., P. dangmechhuensis sp. nov., and P. drukyulensis sp. nov. Molecular data derived from the mitochondrial gene Cyt b and the nuclear gene RAG2 recovered relationships within Parachiloglanis and the Glyptosterninae. A dichotomous key to the Glyptosterninae of Bhutan is provided.